Graft and Corruption Practices Among Selected Public Officials in Mindanao, Southern Philippines - L. LAUT, AMER HUSAIN; G. MARIANO, ABDUL AZIS; B. ONTOLAN, FAY ELAINE; BARACAMONTE, NIMFA L; AGUANO, CHRISTIAN T.N; PONCE, SULPECIA L. (Jurnal Studi Pemerintahan, 2013)
This study aims to examine the graft and corruption practices among selected public officials in southern Philippines. Thestudy is qualitative in nature making use of case study method in which an in-depth analysis of primary data obtained fromeight informants, four of whom are town mayors and their four incumbent municipal treasurers, is employed. The findingsrevealed that the mayor informants got elected through vote buying and bribery. Politics and family matters intersect asinformants are supported by their families during election who used guns, gold and goons to ensure election victory. Theclannish nature of the community finds expression also in the selection of relatives in municipal employment and in accessingmunicipal resources. The most prevalent corruption practice disclosed by the informants is amassing the internal revenueallotment (IRA) for personal purposes in order to recover the huge amount of money spent during election. Other types ofcorruption practices also include falsification of documents, nepotism, bribery, kickbacks, and evasion of public bidding.These public officials also do not seem to perform official duties in their towns as they live outside of their municipalities.Inter-agency involvement of corruption among different government agencies in the areas studied are also uncovered.Moreover, the perceived negative effects of corruption are manifested in the poor delivery of the community’s basic socialservices in health, water supply, education, and security protection. Corruption also adversely affects the construction ofcommunity infrastructure facilities and the establishment of an equitable and solid economic base. The study has implicationsto the strict policy implementation of the provisions of the 1991 Local Government Code of the Philippines, The Anti-Graftand Corrupt Practices Act, and other pertinent laws in order to improve the transparency, integrity and accountability of publicofficials not only in southern Philippines but also in the entire countryKEYWORDS: governance, inter-agency corruption involvement, Internal Review Allotment, maratabat, nepotism